The Red Pony Movie Still - Chas. K. Feldman Group Productions, Incorporated; Republic Pictures; Viacom/Paramount Pictures:::Creator::::::::::::
Billy Buck (Robert Mitchum), Tom, aka Jody Tiflin (Peter Miles) and Grandfather (Louis Calhern) looking off in the distance as Grandfather regales the two with tales about the old west. RESTRICTED USE